Interações CO2-fluido-rocha aplicadas à injeção de fluidos em reservatórios do pré-sal - Pereira, Nalini da Silva (2021)
Enhanced Oil Recovery (EOR) through the injection of seawater is one of the most applied techniques to maintain reservoir pressure after primary depletion, due to the abundance of water in the vicinity of the reservoirs and efficiency for displace the oil. It should be noted that the pre-salt has high amounts of carbon dioxide (CO2) in its composition, and with the global commitment to reduce greenhouse gas emissions, geological storage is a good alternative to avoid damage caused by the emission of this gas. Thus, this work aimed to study pulverized rock samples taken from a pre-salt reservoir, and to simulate the effects of the injection of seawater at high concentrations of CO2, either for advanced oil recovery or geological carbon storage. The interactions were studied through laboratory-scale experiments, simulating the geological conditions in reactors (250 bar CO2 pressure and 60 °C), through the change in the chemical balance inside them through dilutions with injection water, observing the CO2-fluid-rock interaction in reservoir integrity and in advanced oil recovery processes or CO2 geological storage. For the characterization of the rocks before and after the experiments, Scanning Electron Microscopy with Energy Dispersive Spectroscopy (SEM EDS) and X-ray Diffractometry (DRX) were performed. Analyzes of the saline solution before, during and after the experiments were performed by Ion Chromatography and Optical Emission Spectroscopy and Inductively Coupled Plasma (ICP - OES) to identify the ions present in the solution. The results obtained in this study showed variation in mineral dissolution rates throughout the experimental period, with greater evidence in the first hours of reaction. It was not verified the occurrence of precipitation.